Girl in the Mist - Rivers, A. J. (United States A.J. Rivers, 2022)
"There's something strange about the mist... After a night of a scary movie marathon, a cold thick fog rolls over Sherwood, bringing with it the promise of fall. And when FBI Agent Emma Griffin wakes up the next morning, she can't help but shake the feeling that something is off. She turns off her alarm clock, attaches her pager to her hip, and heads out to meet with the agent helping with her newest investigation. There are rumblings through Sherwood. A camp with a sinister past has reopened. There are many different stories about what happened at Camp Hollow twenty years ago, but Emma soon learns the truth is worse than anything told around a campfire. Thirteen bodies then, fifteen now. And one that can't be found. As she unravels local legends and shifts through archives to find out what really happened that stormy night in 1964, she discovers more than just one tragedy... Welcome to Camp Hollow, where gruesome tales come to life" --
"The first book in the Emma Griffin mystery retro - limited series, it can be read as a standalone"--Back cover.
111370
Keywords: United States -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Women detectives -- Fiction; Murder -- Investigation -- Fiction; Camps -- Fiction; Employees; Detective and mystery fiction; Fiction; Thrillers (Fiction)